DAIRY FARMING AND RURAL DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2022)
India is predominantly an agrarian economy with mixed farming involving crop-livestock symbiosis, which has been a way of life since the dawn of civilization, and dairying is the most ancient occupation. 80 million households engaged in dairy farming as their main source of income. Dairying as an essential means of livelihood, provides a regular source of income and employment to rural households. It meets and helps to meet the equity objective of rural development through its contribution to the cash income of small and marginal farmers, also landless labourers. Availability of regular fluid cash from daily sale of milk not only helps in dairying production through purchase of feed and other inputs but also helps in improving crop production through purchase of farm inputs like improved seed, fertilizers and pesticides, cattle raising being a labour intensive activity which provides substantial direct as well as indirect employment. Milk and milk products are second largest contributors to the gross national product next only to paddy. In India, agriculture sector provides livelihood among the food products, demand for milk increases relatively at higher role as education makes people conscious of the value of nutritious food, milk constitutes the most important source of nourishment for both vegetarian and non vegetarian, for old and young alike. At present, India is the largest producer of milk in the world pushing united states to second place. Annual production of milk in India in 2014-2015 was 146 million tones, but it increased to 209 million tonnes in 2020-21 With annual growth rate of about 6.2 per cent, in the same time world total milk production was 843 million tonnes, now India has become major sharing country of milk production in the world, it is 23 per cent. Today India is just not only the global leading milk producer, but it has also become the largest consumer of milk. Dairy development helps in boosting rural economic growth and empowering rural women. , Dairy farming reducing rural poverty, inequity, ensuring food security for millions of rural households, and enhancing economic growth, particularly in rural areas.